Genomic characteristics of Lacticaseibacillus rhamnosus strains isolated from blood - Piotr Jarocki; Jan Sadurski; Martyna Siuda; Mateusz Romanowicz; Jacek Panek; Magdalena Frąc; Adam Waśko (PLoS ONE, 2025)
Lacticaseibacillus rhamnosus is widely recognized for its health-promoting properties, which have led to its broad application in the production of food and dietary supplements. Nevertheless, although rare and typically limited to patients with underlying conditions, adverse effects have also been reported. In this study, we sequenced and characterized the genomes of seven L. rhamnosus strains isolated from blood. Using a hybrid approach that combined Illumina and Oxford Nanopore technologies, we obtained complete genomes ranging from 2.96 to 3.13 Mb, with a GC content of 46.7–46.8%. Comparative analyses with publicly available L. rhamnosus genomes revealed that these isolates were genetically related to strains from highly diverse origins, including plants, dairy products, dietary supplements, the gastrointestinal and genitourinary tracts, as well as blood and other clinical samples from geographically distant regions. Importantly, neither core genome multilocus sequence typing (cgMLST) nor prophage and CRISPR module analyses indicated similarity to the widely used probiotic strain L. rhamnosus GG. Gene-based analysis identified determinants associated with bacteriocin production, adhesion, health-promoting traits, and potential pathogenicity of the strains. Notably, several genes linked to probiotic functions also overlapped with virulence factors found in pathogenic microorganisms. These findings demonstrate the genomic diversity of L. rhamnosus blood isolates and highlight the dual role of certain genetic determinants, underlining the importance of careful strain-level evaluation when selecting L. rhamnosus strains for probiotic use.